The Impact of Data-Driven Approaches on Cyber Security Awareness in Nepal’s Digital Landscape - Gupta, Lokesh; Misra, Dinesh Chandra (Aadim Journal of Multidisciplinary Research, 2025)
Nepal’s increasing reliance on digital platforms has heightened the risks posed by cyber threats such as phishing, malware, and data breaches. Despite growing internet penetration, cyber security awareness remains low among individuals and organizations, leading to significant vulnerabilities. Traditional methods of enhancing awareness, including generic training programs and reactive policies, have proven insufficient to address the evolving nature of cyber threats. These approaches lack personalization and fail to leverage advancements in technology for targeted and proactive solutions. This study aims to explore the impact of data-driven approaches, including machine learning, behavioral analytics, and personalized training, to improve cyber security awareness in Nepal’s digital landscape. The objectives include identifying gaps in existing awareness, analyzing successful global strategies, and recommending actionable, localized solutions. Through leveraging secondary data, the study compares strategies from countries with similar challenges and assesses their applicability to Nepal. The novelty of the research lies in its focus on adapting globally proven data-driven methods to the unique context of Nepal, considering its infrastructure limitations, digital literacy levels, and cultural factors. Findings highlight the effectiveness of personalized training and real-time threat monitoring in enhancing awareness. Recommendations emphasize collaborative efforts between government, organizations, and cyber security firms to implement tailored, data-driven strategies, fostering a more resilient digital environment in Nepal.